ADOPTION OF GOOD AGRONOMIC PRACTICES BY TOMATO FARMERS IN RURAL GHANA: AN APPLICATION OF THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY - Charlotte Akomdo; John-Eudes Andivi Bakang; Enoch Kwame Tham-Agyekum; Ohene Kwasi Yankyerah; Isaac Akese; Sadat Oye; Stephen Prah (Socio-Economics/Agribusiness Department, 2023)
This study uses the Unified Theory of Acceptance and Use of Technology framework to analyze tomato farmers' intention and actual use of good agronomic practices (GAPs). Using a structured questionnaire, data were collected from 300 tomato farmers selected through the multi-stage sampling procedure. Data were analyzed using descriptive and inferential statistics. The results reveal the three practices with the highest level of awareness: fertilizer application, weed control, and pest control. The GAPs practiced mostly by the tomato farmers are fertilizer application, row planting, disease control, and weed control. Results of the Tobit regression model show the extent (intention and actual use) of adoption of GAPs by tomato farmers is influenced by the age of the farmer, years spent in school, years in farming, sources of information, membership of farmer groups, availability of market, performance expectation, and social influence. The results from the study also show that among the major challenges affecting the use of GAPs, lack of credit facilities was ranked first. This study recommends that with the aid of Agricultural Extension Agents, farmers should form cooperatives to enable them to get access to financial support and enable extension workers to easily have access to them.